ACTIVE SAFETY IN THE SYSTEM OF MOTOR-TRANSPORT SAFETY - Stepanov, A.; Степанов, О. В.; Степанов, А. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article considers the impact of active safety on motor-transport safety and on road traffic safety with the purpose of RTA preclusion. The matter of active safety in the system of motor-transport safety is furnished, the main trends in improving traffic safety are determined. While considering the problems of motor transport safety and the problems of improving traffic safety, the need for development of systems that would neutralize any excess control action or even carry out a correction of insufficient control actions of a driver in the «Driver–Vehicle–Road Traffic» system is proven.
АКТИВНА БЕЗПЕКА В СИСТЕМІ БЕЗПЕКИ АВТОМОБІЛЬНОГО ТРАНСПОРТУ
АКТИВНАЯ БЕЗОПАСНОСТЬ В СИСТЕМЕ БЕЗОПАСНОСТИ АВТОМОБИЛЬНОГО ТРАНСПОРТА
Keywords: motor-transport; active safety; road traffic safety; road traffic accidents; driver; vehicle; автомобільний транспорт; активна безпека; безпека дорожнього руху; дорожньо-транспортні пригоди; автомобильный транспорт; активная безопасность; безопасность дорожного движения; дорожно-транспортные происшествия; 656.13